Suicide and depression in adolescence: risk factors and prevention strategies (Research, Society and Development, 2020)
Depressive disorders, which can be identified as one of the fastest growing pathologies in the general population, imply a high mortality degree, especially when it comes to suicide. These disorders also occur in great number among teenagers who see it as a way out of a painful, suffering and desperate. That said, this article aims to discuss the risk factors that can cause depression and culminate in suicide among adolescents and young people, and the manifestations associated with these events. This study is characterized as a narrative literature review, completed in a period of four months, in which articles, books and epidemiologic bulletins were used as research material. We identified as main results that the risk factors responsible for depression and suicide among adolescents include not only psychological questions, but biological and physiological as well. At the end of the study, it was concluded that to prevent those risk factors it is necessary not only the active listening, but also the development of projects that promote health, surveillance and integral healthcare attention.